1998
DOI: 10.1155/mbd.1998.323
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationships for Some Diamine, Triamine andSchiff Base Derivatives and Their Copper(II) Complexes

Abstract: Abstract. Ethylenediamine (en.), putrescine (pu), diethylenetriamine (dien), dipropylenetriamine (dpta), spermidine (spmd) and their Cu 1 compounds as well as the Schiff bases with 2-furaldehyde (dienOO), 2-thiophenecarboxaldehyde (dienSS) and pyrrole-2-carboxaldehyde (dienNN) of dien and that of dpta with 2-thiophenecarboxaldehyde (dptaSS), were prepared and characterised. They were tested against Bacillus substilis, Bacillus cereus, Staphylococcus aureus, Escherichia coli, Proteus vulgar& and Xanthomonas cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Based on the results of elemental analysis, IR, mass spectrometry, electronic spectra, magnetic moment, molar conductance measurements and thermogravimetric analysis, it may be concluded that Schiff base behaves as mononegative NO bidentate ligand, coordination occurring via the azomethine nitrogen and the deprotonated phenolic oxygen atom in position seven of the benzopyran-4-one ring, as shown in Schemes (2,3,4,5).…”
Section: Starink Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the results of elemental analysis, IR, mass spectrometry, electronic spectra, magnetic moment, molar conductance measurements and thermogravimetric analysis, it may be concluded that Schiff base behaves as mononegative NO bidentate ligand, coordination occurring via the azomethine nitrogen and the deprotonated phenolic oxygen atom in position seven of the benzopyran-4-one ring, as shown in Schemes (2,3,4,5).…”
Section: Starink Methodsmentioning
confidence: 98%
“…Especially the complexes of Schiff bases with transition metals which have wide attention because of their diverse biological and pharmaceutical activities [1,2]. Schiff bases offer a versatile and flexible series of ligands capable of binding with various metal ions to give highly remarkable class of complexes having a wide range of applications [3][4][5][6]. So, the investigation of their interaction with various metal ions may contribute to a better understanding of their activities.…”
Section: Introductionmentioning
confidence: 99%
“…The new compounds were prepared by the reaction of the starting materials [Cu(dien)Y 2 ] and Schiff dibase complex [Cu(dienXX)Y 2 ] [18,19,6] with 2a-2tzn. The general procedures are given below.…”
Section: Syntheses Of the Copper(ii) Chelatesmentioning
confidence: 99%
“…Evidently, toxicity should be among the criteria that should be examined before studies of biological activity are undertaken. Continuing our work [4][5][6] on the biological activity of Schiff dibase compounds with S,N-heterocyclic adducts we report the synthesis of a new series of Schiff dibase compounds with 2-amino-2-thiazoline (2a-2tzn), to be of special interest thanks to their antibiotic, anti-inflammatory [7], antifungal [8], anticonvulsant, local anesthetic, fungicidal, bactericidal, herbicidal, insecticidal, antitubercular, cardiotonic, acaricidal, antiulcer, antineoplastic [9][10][11] and antihypertensive [12] properties.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the structure and the chelate ring size of multidentate ligands in coordination compounds is a subject of considerable importance because the coordination chemistry of the metals is affected by the both the type of donor atom and steric requirements [19]. Although salicylidimine ligands and their complexes have been extensively studied in this context, relatively little is known about the Schiff base ligands, especially those derived from pyrrole-2-carboxaldehyde that can potentially act as hexadentate donors [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Previously, we have considered the strain effects in the copper and nickel complexes of two such Schiff base ligands (Scheme 1), each of which possesses an N 2 O 4 donor set [34].…”
Section: Introductionmentioning
confidence: 99%